OSTEOPROTECTIVE MEDICINAL PLANTS - PART 1 (A HUMAN CLINICAL EVIDENCE-BASED REVIEW) - Dragos, Dorin; Gilca, Marilena; Gaman, Laura; Stoian, Irina; Lupescu, Olivera (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background. Osteoporosis is a bone metabolic disease affecting a large percentage of aging population, which leads to an increased risk of fractures and has a negative impact on life quality. The available treatments for osteoporosis are effective, but are associated with several severe adverse reactions, hence the interest for alternative treatments devoid of such redoubtable side effects. Medicinal plants represent a viable resource for new therapeutic agents.The purpose of this review is to provide an overview about the medicinal plants that have been reported to have anti-osteoporotic effects in human clinical studies.Materials and Methods. Relevant studies found in PubMed database, pertaining to efficacy in humans, mechanism of action, osteoactive phytochemicals and safety, were selected. For the inquiry, keywords such as “medicinal plant”, “osteoporosis”, “bone”, “fracture”, “osteoclast” and “osteoblast” were used in various combinations. The information extracted was integrated with the traditional knowledge on the correspondent medicinal plants. Results. Eight medicinal plants (Cimicifuga racemosa, Cissus quadrangularis, Eleutherococcus senticosus, Epimedium spp., Glycine max, Pueraria spp., Panax notoginseng, Salvia milthiorriza) were selected. Mechanisms involved include the activation of osteoblasts, inhibition of osteoclastogenesis, estrogen-like activity, anti-inflammatory activity, inhibition of collagen degradation by cathepsin K.Conclusion. Several medicinal plants have been included in clinical studies successfully targeting osteoporosis, thus showing the potential to modulate bone resorption and bone formation.